Indigenous and Black Confraternities in Colonial Latin America: Negotiating Status through Religious Practices (Routledge, 2022)
This book analyzes indigenous and black confraternal cultural practices as forms of negotiation and resistance shaped by local devotional identities that also transgressed imperial religious and racial hierarchies.